Efektivitas Studi Morfologi terhadap Pemahaman Konsep IPA pada Materi Sel Eukariotik Pada Mahasiswa PGSD Universitas Harkat Negeri - Ririn Hestiningtyas; Istiqomah Istiqomah; Azzumardin Syaidi (JURNAL PENDIDIKAN, 2026)
This study aims to determine the effectiveness of morphological studies on the understanding of science concepts in the material of eukaryotic cells of elementary school teacher education students at Harkat Negeri University. The study used a quantitative approach with a quasi-experimental design of one group pretest-posttest. The research sample consisted of 44 students selected using purposive sampling. The research instruments were in the form of a concept understanding test, observation, and documentation. The results showed an increase in the average score of students from 54.37 in the pretest to 90.58 in the posttest with an increase of 36.21%. The results of the paired sample t-test showed a significance value of 0.000 <0.05 so that morphological studies were declared effective in improving students' conceptual understanding. Learning based on morphological studies helps students understand the structure and function of cell organelles in a more concrete, visual, systematic, and meaningful way.